(untitled) (Journal of Economic Research & Business Administration, 2015)
The value of enterprise, as motive force of new economy, was underline in Message 2013 year of President of Kazakhstan. Small business entities from the limit scales and resources appear in less advantageous position at the market, what major concerns with that small and midsize businesses can not compete on equal. In Republic of Kazakhstan development of enterprise is one of priority directions of economic politics of the state oriented to creation of new hi-tech productions with a most valueadded. The sphere of enterprise remains one of key mechanisms of activation of socio-economic life of society. Small and middle enterprises assist the height of competitiveness and economy.